Structural performance of orthotropic Steel-Concrete continuous composite decks with larger U-ribs and PBL shear connectors. (May 2023) - Shan, Yulin; Chen, Yuli; Zong, Zhouhong; Li, Jiaqi; Li, Zhuo; Xu, Yousheng
Abstract: This study investigates the structural performance of the OSCCCDs with larger U-ribs and PBL shear connectors. Four OSCCCDs with larger U-ribs and PBL shear connector specimens were fabricated and tested under a static load, in which the experimental parameters were the spacing of the PBL shear connector and the spacing of the holes of the PBL shear connectors. Parametric analysis via finite element models was also carried out to explore the effects of the reinforcement ratio, the thickness of the steel plate, the thickness of the U-ribs, the thickness of the concrete slab, and the hole diameter of the PBL shear connector on the structural performance. It can be concluded from the experimental and numerical results that the OSCCCDs exhibited higher bearing capacity and better ductility. The OSCCCDs exhibited flexure failure at the mid-span and diagonal tension failure at the intermediate supports. The thickness of the U-ribs and the thickness of the concrete slab showed the highest impact on the initial stiffness and ultimate load of the OSCCCDs, followed by the spacing of the PBL shear connectors and the spacing of holes in the PBL shear connectors. The reinforcement ratio, the thickness of the steel plate, and the hole diameter of the PBL shear connector had little influence on the initial stiffness and ultimate load of the OSCCCDs. Finally, a simplified flexural analysis method can be proposed to accurately predict the elastic deflection and ultimate bending moment of the OSCCCDs under the service loads, respectively. The maximum absolute discrepancies of the elastic deflection and ultimate bending moment of the theoretical results are 8.2% and 12.0% by validating against the experimental and numerical results within the investigated ranges of parameters, respectively.